The origin of chow chows in the light of the East Asian breeds. (December 2017) - Yang, Hechuan; Wang, Guodong; Wang, Meng; Ma, Yaping; Yin, Tingting; Fan, Ruoxi; Wu, Hong; Zhong, Li; Irwin, David; Zhai, Weiwei; Zhang, Yaping
Abstract Background East Asian dog breeds are one of the most ancient groups of dogs that radiated after the domestication of the dog and represent the most basal lineages of dog evolution. Among these, the Chow Chow is an ancient breed that embodies very distinct morphological and physiological features, such as sturdy build, dense coat, and blue/purple tongue. Results Using a Restricted site Associated DNA (RAD) sequencing approach, we sequenced the genomes of nine Chow Chows from China. Combined with a dataset of 37 canid whole genome sequencing (WGS) from several published works, we found that the Chow Chow is one of the most basal lineages, which originated together with other East Asian breeds, such as the Shar-Pei and Akita. Demographic analysis found that Chow Chows originated from the Chinese indigenous dog about 8300 years ago. The bottleneck leading to Chow Chows was not strong and genetic migration between Chow Chows and other populations is low. Two classes of genes show strong evidence of positive selection along the Chow Chow lineage, namely genes related to metabolism and digestion as well as muscle/heart development and differentiation. Conclusions Dog breeds from East Asia, including the Chow Chow, originated from Chinese indigenous dogs very early in time. The genetic bottleneck leading to Chow Chows and migrations with other populations are found to be quite mild. Our current study represents an early endeavor to characterize the origin of East Asian dog breeds and establishes an important reference point for understanding the origin of ancient breeds in Asia.